Development of Arabic Scrabble Game to Improve Arabic Vocabulary for Students of Arabic Education Study Program IAIN Jember - Evi Muzaiyidah Bukhori; Ahmad Sulton (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to develop an Arabic Scrabble game product to increase Arabic vocabulary, describe the steps for developing an Arabic Scrabble game, and test the feasibility of an Arabic Scrabble game development product to improve Arabic vocabulary. This type of research is Research and Development research with the Borg and Gall development model which is modified into five steps of development, namely 1) Research and data collection (2) Formulating a research plan. (2) Development of initial product draft. (4) Test the product to the validator. (5) Revision. The instruments used were expert validation questionnaires (media, material and language experts) and interview guidelines. The results showed that the Arabic Scrabble game was categorized as a very appropriate learning media to be used in learning Arabic vocabulary. This can be seen from the results of the research (1 steps for making a game consisting of a game box/packaging, game board, game chips/dice, letter rack, game manual and game assessment sheet. (2 Based on the results of expert trials, game product development Arabic Scrabble got a score of 95.3% (very decent category) from media experts, material expert validation got a score of 86% (decent category), linguist validation got a score of 96% with (very decent category).